2014
DOI: 10.1111/jgh.12519
|View full text |Cite
|
Sign up to set email alerts
|

Controlled attenuation parameter for the detection of steatosis severity in chronic liver disease: A meta‐analysis of diagnostic accuracy

Abstract: CAP has good sensitivity and specificity for detecting hepatic steatosis; however, based on a meta-analysis, CAP was limited in their accuracy of steatosis, which precluded widespread use in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
105
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 43 publications
6
105
2
3
Order By: Relevance
“…A major limitation of CAP is its failure rate, which occurred in approximately 20% of the patients with NAFLD [13]. This was higher than that reported for other etiologies of liver disease where the rate was 7.7% [15].…”
Section: Controlled Attenuation Parametercontrasting
confidence: 49%
See 2 more Smart Citations
“…A major limitation of CAP is its failure rate, which occurred in approximately 20% of the patients with NAFLD [13]. This was higher than that reported for other etiologies of liver disease where the rate was 7.7% [15].…”
Section: Controlled Attenuation Parametercontrasting
confidence: 49%
“…A meta-analysis including nine studies assessing CAP in patients with chronic liver disease of varying etiologies found overall summary sensitivity and specificity values of 78 and 79% for ≥ S1, 85 and 79% for ≥ S2 and 83 and 79% for S3 [13]. A limitation of this study was that CAP cut-off values were different across the studies and were not validated [13].…”
Section: Controlled Attenuation Parametermentioning
confidence: 95%
See 1 more Smart Citation
“…85%-os érzékenység és 79%-os fajlagosság mutatkozott 11-33%-os elzsírosodás esetén. 67-100%-os steatosis esetén 83%-os érzékenységet és 79%-os fajlagossá-got közöltek [54]. A májbiopsziához képest 100-szor nagyobb májszövetet jellemez.…”
Section: Controlled Attenuation Parameter (Cap)unclassified
“…In a recent meta-analysis [68] assessing the CAP accuracy for steatosis detection, the summarized sensitivity and specificity values were 0.78 (95% confidence In comparison to other modalities, CAP is non-invasive, quantitative, and non-ionising. Furthermore, the procedure is easy to perform and provides immediate results; it is also machine-independent and does not require corrections to be made for gain, frequency, focusing or beam diffraction, and is also not subject to operator interpretation [65].…”
Section: Controlled Attenuation Parameter (Cap)mentioning
confidence: 99%